Pentingnya Pendidikan Adab dalam Pembentukan Karakter Siswa di SMP Muhammadiyah 49 Medan - Rambe, Nadiatul Ulyah (Integrasi: Jurnal Studi Islam dan Humaniora, 2024)
Character education plays a vital role in shaping students' personalities, especially in secondary schools. This study aims to explore the importance of adab education in character formation at SMP Muhammadiyah 49 Medan. Adab education not only includes moral and ethical teachings but also involves instruction on good behavior, manners, and responsibility. This research employs a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation. The findings reveal that the adab education implemented at SMP Muhammadiyah 49 Medan significantly contributes to enhancing students' positive attitudes and behaviors, such as respect, discipline, and responsibility. Additionally, the application of adab education also helps create a harmonious and conducive school environment for students' character development. This study provides valuable insights into the importance of adab education in character building at the secondary school level.